Comparison of a Pure Plug-Based Versus a Primary Suture-Based Vascular Closure Device Strategy for Transfemoral Transcatheter Aortic Valve Replacement: The CHOICE-CLOSURE Randomized Clinical Trial. Issue 3 (5th November 2021) - Abdel-Wahab, Mohamed; Hartung, Philipp; Dumpies, Oliver; Obradovic, Danilo; Wilde, Johannes; Majunke, Nicolas; Boekstegers, Peter; Müller, Ralf; Seyfarth, Melchior; Vorpahl, Marc; Kiefer, Philipp; Noack, Thilo; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Transcatheter aortic valve replacement is an established treatment option for patients with severe symptomatic aortic stenosis and is most commonly performed through the transfemoral access route. Percutaneous access site closure can be achieved using dedicated plug-based or suture-based vascular closure device (VCD) strategies, but randomized comparative studies are scarce. Methods: The CHOICE-CLOSURE trial (Randomized Comparison of Catheter-based Strategies for Interventional Access Site Closure during Transfemoral Transcatheter Aortic Valve Implantation) is an investigator-initiated, multicenter study, in which patients undergoing transfemoral transcatheter aortic valve replacement were randomly assigned to vascular access site closure using either a pure plug-based technique (MANTA, Teleflex) with no additional VCDs or a primary suture-based technique (ProGlide, Abbott Vascular) potentially complemented by a small plug. The primary end point consisted of access site– or access-related major and minor vascular complications during index hospitalization, defined according to the Valve Academic Research Consortium-2 criteria. Secondary end points included the rate of access site– or access-related bleeding, VCD failure, and time to hemostasis. Results: A total of 516 patients were included and randomly assigned. The mean age of the study population was 80.5±6.1 years, 55.4% were male, 7.6% of patients had peripheral vascular disease, and the mean Society of Thoracic Surgeons score was 4.1±2.9%. The primary end point occurred in 19.4% (50/258) of the pure plug-based group and 12.0% (31/258) of the primary suture-based group (relative risk, 1.61 [95% CI, 1.07–2.44], P =0.029). Access site– or access-related bleeding occurred in 11.6% versus 7.4% (relative risk, 1.58 [95%CI: 0.91–2.73], P =0.133) and device failure in 4.7% versus 5.4% (relative risk, 0.86, [95% CI, 0.40–1.82], P =0.841) in the respective groups. Time to hemostasis was significantly shorter in the pure plug-based group (80 [32–180] versus 240 [174–316] seconds, P <0.001). Conclusions: Among patients treated with transfemoral transcatheter aortic valve replacement, a pure plug-based vascular closure technique using the MANTA VCD is associated with a higher rate of access site– or access-related vascular complications but a shorter time to hemostasis compared with a primary suture-based technique using the ProGlide VCD. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT04459208.